Development and characterization of AA6063 matrix composite reinforced with B4C, graphite and groundnut shell powder. (2023) - Kumar Singh, Pritish; Thakur, Anupam; Rana, Ramakant; Lal, Roop
Abstract: In due course of time, the role of natural reinforcement for Aluminium matrix composites (AMCs) composite manufacture has gained the interest of many researchers. It is cost-effective and at the same time environmentally friendly as it helps in the use of certain disposable or pollution creating substances. The manufacturing of various automotive parts, biomedical, and aerospace parts can be done by using these naturally occurring fibers or particulates. An effort has been made to study the effect of such industrial waste on the Aluminium metal matrix composite and evaluate it in terms of characterization. A comparison has also been made with solid lubricant reinforcement and compares wear for both types of composite. The focus of this study is on the characterization of the AA 6063 reinforced hybrid composite with desired material produced using stir casting. The AA 6063 is fabricated with the composition of B4 C + Graphite (Gr.) and B4 C + Groundnut Shell Powder (GSA) composition. The hybrid composite constituting hybrid composite of two types has been formed i.e. Al6063 + 6 %B4 C + 4 % Gr and Al6063 + 6 %B4 C + 3 % GSA. FeSEM images revealed the homogenous composition of the reinforcement particles. A tribological study revealed the average wear rate of 67.14 µm for Al6063 + 6 %B4 C + 3 % GSA and 60.02 µm Al6063 + 6 %B4 C + 4 % Gr. Microscopic images of the worn samples of composite reveal that both show good wear resistance, more for Gr. reinforced composite followed by SBA, the reason being the self-lubricating property of the Gr. reinforced hybrid composite. Thus as a result it can be cost-effective to find certain automotive applications where strength to weight ratio is a key factor to look at.